2002
DOI: 10.1038/sj.jp.7210775
|View full text |Cite
|
Sign up to set email alerts
|

Successful Perinatal Management of Hydrops Fetalis Due to Hemolytic Disease Associated with D−− Maternal Phenotype

Abstract: We report the successful management of a case of hemolytic disease and hydrops fetalis secondary to anti Rh 17 antibodies in a woman with the rare D-- phenotype. We discuss the efficacy of intravenous immunoglobulins in treating hemolytic disease of the newborn infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…There has been a report on a patient treated with 0.5 g/kg of immunoglobulin added to 20 mL/kg of packed RBC [16]. Although fetal transfusion is usually possible at the 22nd gestational week, it is technically challenging and incurs the risk of developing bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a report on a patient treated with 0.5 g/kg of immunoglobulin added to 20 mL/kg of packed RBC [16]. Although fetal transfusion is usually possible at the 22nd gestational week, it is technically challenging and incurs the risk of developing bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Blood exchange not only rids serum of uncombined bilirubin in large quantities, thus lowering serum bilirubin concentration, and preventing occurrence of kernicterus, but also corrects anemia and prevents cardiac failure. Yet, success of such management is also limited in individual case reports 2,3 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, success of such management is also limited in individual case reports. 2,3 For the fetus, the middle cerebral artery Doppler flow is non-invasive and considered the best test for assessing fetal anemia. In this case, with the parturient at 35 weeks gestation and evidence of placental insufficiency, we did not feel that a Doppler flow study was necessary as delivery was nevertheless indicated.…”
Section: Discussionmentioning
confidence: 99%
“…In Western populations, -D-/-D-is an extremely rare Rh phenotype, with only 3 cases of hemolytic disease of the fetus and newborn in sensitized -D-/-D-women reported in the English language literature [2][3][4]. On the other hand, the frequency of the -D-/-D-phenotype among Japanese is much higher (approximately 1 in 100,000) and 50 cases of hemolytic disease of the fetus and newborn in -D-/-D-women have been reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases were found in English language reports and 50 cases in Japanese literature, of which prenatal diagnosis was made in 2 and 5, respectively [3,4,[7][8][9][10][11]. Those 7 cases and the present one are summarized in table 1.…”
Section: Review Of the Literaturementioning
confidence: 99%